Marcação de antiveneno escorpiônico com tecnécio-99m e a suabiodistribuição em ratos de 21-22 dias - Dayana Sampaio Cardoso (2007)
The frequency that accidents with scorpions occur in some regions of Brazil constitutes a problem of public health, mainly in Minas Gerais and São Paulo. The species Tityus serrulatus, the yellow scorpion, is considered the most venomous of South America, due to high toxicity of its venom, showing serious damage in accidents with children. Theimmunotherapy, considered the only specific treatment for the envenomation, has been considered for some researchers as indispensable, but inefficient for others in relation to the prevention and blockade of venom-induced cardiovascular manifestations, mostly inchildren. Due to the tityustoxin, the highest venom toxic protein of T. serrulatus, shows different body distribution between adult rats (150-160 days-old) and young rats (21-22 days-old), and the absence of information about body distribution of the antivenom in young animals, the antivenom produced by Fundação Ezequiel Dias (Funed) waslabeled with 99mTechnetium to study of body distribution in young rats (21-22 days-old). The labeling was made using two reducing agents, the stannous chloride and sodium borohydride. The purification was made by filtration using cellulose ester membrane. A labeling yield of 98.32±0.69% was obtained after the purification. The labeling yield afterincubation with PBS pH 7.4 at 37 °C remained constant showing that stability of 99mTc- F(ab) 2 was preserved. The maintenance of the antivenom activity after labeling with 99mTc was verified in vivo and in vitro. In vivo, the potency was determined and compared with unlabeled antivenom. It was not observed any statistical difference between potencies of unlabeled (1.21 mg/mL), and labeled (1.12 mg/mL) antivenom. In vitro the immunoreactivity of 99mTc-F(ab)2 was verified using affinity chromatograph. 99mTc-F(ab)2 presented specific bound with venom. The process of labeling did not cause protein fragmentation as demonstrated by SDS-PAGE electrophoresis. The labeling process was efficient and the technetium99m labeled scorpion antivenomcould be safely used for body distribution studies. The labeled scorpion antivenom in 21- 22 days-old rats reached a maximum uptake in kidneys, followed by spleen, liver, heart, lung, thyroid and brain. The uptake of the specific fraction was unexpectedly observed in brain. AUC 0 - 24 h were larger to kidneys and blood, and smaller to brain when comparedwith other organs. Just kidneys showed value of Kp larger than one. These results indicated that the antivenom stays more time in blood and has a renal elimination. Differences were verified between profiles of uptake of F(ab')2 and of the tityustoxin in the same organs of young animals. The comparison of the tmax values and Kp for F(ab')2and tityustoxin showed that F(ab')2 is distributed slower for the organs than the tityustoxin. The decline phase still is happening after 24 hours of specific fraction administration, differently of the venom that was almost completely eliminated. In conclusion, F(ab')2 was distributed from the blood to target organs of the envenomation, including the brain, however in different amounts and periods than the venom. It may compromise the antivenom effectiveness, depending on the concentration of the fractionthat specifically binds to the venom and the time elapsed after the sting.